Digital Transformation of Myna Gawosa Fisheries MSMEs: AOV Analysis and Sales Improvement Strategies Post E-Commerce Implementation - Christy Mahendra; Yosita Lianawati; Wilibrodus Megandika Wicaksono; Jonathan Briant Wijaya; Agnes Florentina Santosa; Maria Putri Kinanti (Universitas Lambung Mangkurat, 2026)
This report presents an analysis of e-commerce performance as a result of the community service program (Pengabdian Masyarakat/PkM) at the Myna Gawosa Fish Cultivators Group (Pokdakan), Banjarnegara. The objective of this community service program is to address the limitations of conventional marketing through the implementation of e-commerce-based digital marketing technology to expand market reach and improve the welfare of fish farmers. The PkM implementation method is carried out in stages, including program socialization, digital literacy and content creation training, e-commerce technology application, as well as mentoring and periodic evaluation. The target of the PkM activities is the Myna Gawosa Farmers Group, which cultivates ornamental and consumption fish. Overall, the digital platform shows a positive impact on business volume: Total Revenue grew significantly by 36.8%, driven by a sharp increase in the Number of Orders by 120.0%. However, this success is offset by a drastic decrease in the Average Order Value (AOV) by -37.8%. In conclusion, the business successfully drove transaction volume but faces three major strategic issues: daily revenue volatility, declining AOV, and a customer base that is too small. Strategic recommendations include the development of upselling and cross-selling techniques, as well as more intensive digital marketing campaigns for acquiring new customers.